Exploring AI-powered personalized learning in universities - Agatova, Olga; Latipova, Liliya (Institute of Advanced Engineering and Science, 2025)
The study examines the problem of implementing and developing personalized learning with the help of artificial intelligence (AI) tools in universities. To solve this problem, the following goals were set: identifying the opportunities for personalized learning based on learning tools powered by AI according to university teachers; examining the current state of AI-powered learning technologies using the example of two developing countries; and clarifying the existing challenges and prospects. The study uses a survey and an interview. The results indicate that 82% of the respondents were generally aware of AI and personalized learning. The findings show that 89% of the teachers disagreed with the idea that AI and personalized learning have the potential to replace traditional educational strategies. The teachers identified several challenges, such as the lack of personal communication and difficulties with recognizing emotions, in the proposed strategies. Thus, 43% of the respondents suggested integrating AI into the educational process as a supplement to the traditional teaching methods. The analysis of interviews revealed that 85% of the teachers were positive about the implementation of AI and personalized learning in universities. Nevertheless, educators report that AI-generated tools are still underdeveloped and cannot replace all functions of teachers.